Jean Rhys et Shani Mootoo ou la fragmentation de l’être - Freddy Marcin (Revue LISA)
Identity in a colonial context cannot be defined through singularity. It has to be redefined through a multiplicity of origins. The human being thus becomes a mosaic of smaller identities struggling against inner trouble. This inevitable fight leads him/her towards implosion. Madness thus remains the only way out of a demanding and masculine world. In this article, we will study fragmented identities in Wide Sargasso Sea by Jean Rhys and Cereus Blooms At Night by Shani Mootoo. Feminine identity crisis will be analyzed in correlation with narrative strategies used in post-colonial and queer literatures as well as deconstruction and subversion of literary canons.